1995
DOI: 10.1177/019372395019001004
|View full text |Cite
|
Sign up to set email alerts
|

Sport, Physical Danger, and Injury: The Experiences of Elite Women Athletes

Abstract: For a long time, rugby union was reserved for men in France. The French rugby union federation only opened its doors to women in 1989. Twenty years later, we asked ourselves how and when women start playing rugby and if there are still social barriers to their practice. In order to answer this, we interviewed 15 persons who belong to the world of French rugby and almost 200 female players. The results show that people around the players are reserved, mainly for fear of the physical risk, the injuries they asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
2
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 18 publications
(1 reference statement)
3
80
2
7
Order By: Relevance
“…Again, as might be expected, this bears a striking resemblance to studies of professional athletes which have found that injury and pain are normalized, and often hidden, in elite performers (Curry, 1993;Young and White, 1995;Young et al, 1994).…”
Section: Fractured Identities: Some Sequelae Of Dance Injurysupporting
confidence: 79%
See 1 more Smart Citation
“…Again, as might be expected, this bears a striking resemblance to studies of professional athletes which have found that injury and pain are normalized, and often hidden, in elite performers (Curry, 1993;Young and White, 1995;Young et al, 1994).…”
Section: Fractured Identities: Some Sequelae Of Dance Injurysupporting
confidence: 79%
“…This is similar for other athletes, and the sociology of sport provides some helpful insights into elite, high performance bodies and into the significance of injury and retirement within particular sporting subcultures (Laker, 2002;Leonard, 1993). For instance, several studies of professional sports have found that serious injury can have a major impact on the identity of elite athletes (Curry, 1993;Young and White, 1995;Young, White and McTeer, 1994). …”
Section: Fractured Identities: Some Sequelae Of Dance Injurymentioning
confidence: 99%
“…Young & White, 1995;Young et al, 1994). In relation to this study, although there were undoubted differences between myself and my male running partner in our experiences of, and responses to our knee injuries, detailed analysis of the data did not suggest that gender was a significant variable in this particular case.…”
Section: Biographical and Injury Contextcontrasting
confidence: 57%
“…Second, much research focuses upon athletes unable to attain their preinjured sporting status, (Sparkes, 1996(Sparkes, , 1998Brock & Kleiber, 1994;Young & White, 1995), whereas this study charts the successful transition from injured sporting body to the rehabilitated state. Third, many recent qualitative studies are based on interviews with injured athletes (Brock & Kleiber, 1994;Sparkes,1998) or recounting the researcher's own experiences of sport injury and rehabilitation (Sparkes, 1996(Sparkes, , 1999Sparkes & Silvennoinen, 1999) post hoc.…”
mentioning
confidence: 99%
“…Studies, for example, have revealed how rugby can produce pleasure via: bruising physicality and involvement in a mock battle (Chase, 2006;Elias & Dunning, 1986;Sheard & Dunning, 1973;Young & White, 1995); inducement of friendships and team work (Carle & Nauright, 1999); development and display of skill, fitness and strategy (Chu, Leberman, Howe, & Bachor, 2003;Light, 2007); physical contact and intimacy (White & Vagi, 1990;Gard & Meyenn, 2000); affirming and/or challenging gendered identities (Chase, 2006;Donnelly & Young, 1985;Dunning, 1986;Price & Parker, 2003;Pringle & Markula, 2005;Wheatley, 1994) and televisual voyeurism (Star, 1992). These rugby pleasures span a broad array yet are typically cited in secondary relation to a social issue.…”
Section: Rugby and The Marginalization Of Pleasurementioning
confidence: 99%